Peri-intubation cardiac arrest in emergency department of a tertiary care hospital, Nepal - Dhital, Kapil Raj; Samal, Anup Mangal (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Peri-intubation cardiac arrest leads to morbidity and mortality. Patients present in emergency department with various presentations such as difficult intubation, refractory shock, respiratory distress and are at risk of complications like failed intubation and cardiac arrest. Cardiac arrest can be reduced if we treat physiological changes prior to intubation. This study aims to explore the peri-intubation cardiac arrest and its relation with physiological state of the patient.Method: This was an observational-analytic-cross sectional study from secondary data conducted at Patan Academy of Health Science emergency department. The data source was emergency airway registry of Patan Academy of Health Sciences which started in Jan 2022. The available data till Feb 2024 was taken for the study.Result: Total 196 patient underwent emergency intubation in study period, among them 31 cases (15.8%) developed peri-intubation cardiac arrest and mean age of cardiac arrest is 56 year and male to female ratio of cardiac arrest is 1.2:1. First pass intubation success rate is 61.73%. Nine hypotensive cases, 12 hypoxemic cases, 8 hypotensive as well as hypoxemic cases and 2 cases of neither hypotensive nor hypoxemic develop peri-intubation cardiac arrest.Conclusion: Peri-intubation hypotension and hypoxemia are two main physiologically compromised states that is associated with peri-intubation cardiac arrest. The likelihood of cardiac arrest during emergency intubation decreases significantly if the tube is successfully inserted on the first attempt.